The Victim-Perpetrator Relationship and Peritraumatic Schemas as a Result of Sexual Trauma - Lauricella, Danielle (Journal of interpersonal violence, 2023)
The development of posttraumatic stress symptoms (PTSS) due to sexual trauma is complex. Various mechanisms have been studied to explain the relationship between sexual trauma and PTSS. Other studies have looked at the impact of the victim-perpetrator relationship on the relationship between sexual trauma and PTSS with mixed results. Lacking from the literature is the possible mediating effect of peritraumatic schemas for the relationship between sexual trauma and PTSS. Additionally, the impact of the type of victim-perpetrator relationship may have on the development of peritraumatic schemas has also been unaddressed. This study seeks to close the gap in the literature by asking if peritraumatic schemas mediate the relationship between sexual trauma, specifically attempted and completed rape, and PTSS. The moderating role of the victim-perpetrator relationship on the association between sexual trauma and peritraumatic schemas was also examined. Using a college student sample that had endorsed experiencing at least one sexual trauma in their life, this study examined path analysis model explaining the mediating effects of peritraumatic schemas and the moderating effects of the victim-perpetrator relationship. Results indicated that peritraumatic schemas partially mediated the relationship between attempted rape and PTSS when controlling for completed rape. This effect was not found for the relationship between completed rape and PTSS when controlling for attempted rape. The interaction between attempted rape and the acquaintance perpetrator relationship was significant, indicating that peritraumatic schemas increased more severely for those that experienced attempted rape by an acquaintance. Recognizing that PTSS partially results from the peritraumatic schemas experienced, which are impacted by the victim-perpetrator relationship, helps increase understanding of the experience of attempted rape.